Using Homo-Separation of Variables for Solving Systems of Nonlinear Fractional Partial Differential Equations - Abdolamir Karbalaie; Hamed Hamid Muhammed; Bjorn-Erik Erlandsson (International Journal of Mathematics and Mathematical Sciences)
A new method proposed and coined by the authors as the homo-separation of variables method is utilized to solve systems of linear and nonlinear fractional partial differential equations (FPDEs). The new method is a combination of two well-established mathematical methods, namely, the homotopy perturbation method (HPM) and the separation of variables method. When compared to existing analytical and numerical methods, the method resulting from our approach shows that it is capable of simplifying the target problem at hand and reducing the computational load that is required to solve it, considerably. The efficiency and usefulness of this new general-purpose method is verified by several examples, where different systems of linear and nonlinear FPDEs are solved.